The impact of Medicaid expansion on asthma-related health care services utilization and expenditure - Shi, Lu; Yoon, Jangho; Li, Tao; Jeff, Luck (The Journal of asthma, 2023)
The purpose of this study was to examine the effect of Medicaid expansion on asthma-related health care services utilization and expenditures among low-income adult patients with asthma aged 26-64. Using a pooled dataset from 2007 to 2018 Medical Expenditures Panel Surveys (MEPS), we implemented a multivariate difference-in-differences analysis, which compared changes in utilization and expenditures for asthma-related health care services among adult patients with asthma with income below 133% Federal Poverty Level (FPL) vs. above 133%-400% FPL, before and after Medicaid expansion in 2014. We used negative binomial models to analyze utilization outcomes. Expenditures were estimated using two-part models with logit as the first part and generalized linear models as the second part. Estimates were weighted for the complex multi-stage sampling design of MEPS. Medicaid expansion was associated with increases in both utilization and expenditures for asthma-related prescription drugs among low-income patients with asthma, by 1.8 prescription fills (p < 0.05) and $233 (p < 0.05) per year, respectively. No statistically significant association was detected for other asthma-related health care services. Medicaid expansion led to an increase in accessibility of prescription drugs among low-income asthma patients, but had no effect on other asthma-related health care services.